How Do WE Address the Instructors in the Expanding Circle? Perspectives from Turkish EFL Speakers - Ahmet Can Uyar; İsmail YAMAN (Dilbilim Araştırmaları Dergisi)
This paper explores the linguistic forms preferred by Turkish speakers of English to address instructors in academic settings. Far from the norm-referenced approach which focuses on labeling non-native-like practices as failures, this study casts light on the underlying mechanisms of the identified address preferences from a variationist point of view. To this end, 140 Turkish speakers of English as a foreign language reported the address forms they preferred on a discourse completion task. Next, ten participants were semi-structurally interviewed to reveal the motives behind their preferences. The results yielded that Turkish language and culture were mirrored on L2 English address practices through code-switching and translating. Along with the finding that the participants repudiated the address norms of the Inner Circle varieties of English, it was discussed that this can be a sign of a developing system of addressing in Turkish English as a variety in the Expanding Circle.